THE INFLUENCE OF INTERPERSONAL COMMUNICATION AND TEAMWORKON EMPLOYEE PERFORMANCE IN THE FOOD SECURITY SERVICEDELI SERDANG REGENCY - Lulu Yonika; Nur M Ridha Tarigan; Aminuddin (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
The formulation of the problem in this study is what is the effect of Interpersonal Communication on employee performance. What is the effect of Teamwork on employee performance. What is the effect of Interpersonal Communication and Teamwork on Employee Performance. This study aims to determine and analyze the Effect of Interpersonal Communication and Teamwork on Employee Performance at the Food Security Service of Deli Serdang Regency. This research was conducted at the Food Security Service of Deli Serdang Regency located in the Deli Serdang Government Area, Lubuk Pakam District. The objects in this study are Interpersonal Communication as variable X1 and Teamwork as variable X2 on Employee Performance as variable Y. The research time was conducted from November 2024 to April 2025. The population and sample in the study amounted to 50 employees. Data collection techniques are questionnaires (questionnaires), interviews, document studies and literature studies. Data are processed using SPSS version 27. Data analysis in this study uses data quality tests, classical assumption tests, multiple linear regression tests, and hypothesis tests. Based on the results of the study, it can be concluded that Interpersonal Communication has a positive and significant effect on employee performance. Teamwork has a positive and significant impact on employee performance. Interpersonal communication and teamwork have a positive and significant impact on employee performance.